O mal da imagem (?) e as estratégias de apropriação em "Mouchette.org" - Santos, Rodrigo Hipólito dos (2015)
From the artistic proposal "Mouchette.org" (1996) authored by Martine Neddam, this dissertation deals with net.art features focused on the sharing and interactivity. It is our interest better understand the transformations that occurred in personal repres